Pulmonary Manifistation of Systemic Lupus Erthymatosus Sle. - Dr. Rana Sami Hameed; Dr. Sabreen Ghazi Abed; Dr. Mahmood Fouad Mahmood (Zien Journals, 2023)
Systemic lupus erythematosus is a rare complex autoimmune disease with multisystem involvement. SLE may affect all components of the respiratory system alveoli, airway, interstitum and respiratory muscle
Keywords: pulmonary manifestation; Systemic lupus erythematosus; HCV